YIELD AND YIELD ATTRIBUTES OF MAIZE AS INFLUENCED BY GRADED LEVELS OF PHOSPHORUS FERTILIZATION IN SALT AFFECTED SOILS - MANIMARAN, M.; POONKODI, P. (Annals of Agricultural Research, 2014)
A field experiment was conducted in three soils viz., normal, saline and sodic to optimize the best level of P for the maize variety Ganga. Seven levels of P viz., 0, 75, 100, 125, 150, 175 and 200 % recommended dose of P2O5 ha (RDP) in the form of super phosphate were added in each of the three soils. The results revealed that grain yield increased with increase in the levels of P application from 0 to 200% RDP in normal as well as in saline and sodic soils. However application of P @ 100% RDP in normal soil exhibited significant effect on grain yield (4.82 t/ha. But in case of saline and sodic soils, application of 125% RDP recorded significant effect on grain yield (4.00 t/ha in saline soil and 3.91 hal in sodic soil). A similar trend was observed in straw yield also. The yield attributing characters such as double cobs%, length and girth of the cob, 100 grain weight increased with increasing levels of P up to 100% RDP in normal soil and 125% RDP in saline and sodic soils. Thereafter no significant difference was observed with higher levels of P.